HISAB HAKIKI: Metode Ilmiah Penentuan Awal Bulan Kamariyah - Alimuddin, Alimuddin (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2020)
Essential reckoning is one method of determining the beginning of the Kamariyah month, calculations performed with accurate astronomical data. The calculation results are also accurate and can be tested for validity or proven valid. In practice, the ultimate reckoning is divided into two systems, ijtima system and hilal position system.